Bioaugmentation of microbes to restore coastal wetland plants to protect land from coastal erosion. (September 2016) - Bledsoe, Regina; Boopathy, Raj
Abstract: Microbes with beneficial effects to plant growth and health have been dubbed plant growth-promoting rhizobacteria (PGPR). PGPR has been extensively studied in crop plants; however, our study investigates the effects of PGPR on the wetland grass Spartina alterniflora . S . alterniflora is the dominant vegetation in coastal marshes and is often used in wetland restoration projects. Greenhouse raised S . alterniflora were subjected to three treatments: One of a consortia of microbes with freshwater, one of a consortia of microbes with 10 parts per thousand (ppt) saline water, and one with a pure culture and freshwater. Plant growth and soil nitrogen and phosphorus content were measured over 60 days and all plants were sacrificed at the end of the experiment to quantify biomass. Of the three treatments, the treatment receiving the consortia plus salt water had the most growth (41.1 ± 4.4 cm) and greatest biomass (108.03 g) followed by the pure culture treatment with freshwater (34.9 ± 3.2 cm, 96.25 g), the consortia treatment with freshwater (39.7 ± 5.0 cm, 89.04 g), and lastly the control treatment (7.7 ± 1.5 cm, 51.85 g). All treatments were significantly different from the control but not significantly different between each other. In consortia plus 10% saline water treatment, mean stem growth was almost six times greater, total biomass was doubled, and the number of additional stems was three times greater compared to the control. This study shows a positive relationship between microbial activity, soil nutrient cycling of nitrogen and phosphorus, and plant growth in greenhouse grown S . alterniflora inoculated with PGPR. Highlights: Bioaugmentation method was used to enhance coastal plant growth. Microbial consortium in the presence of 10 ppt salinity enhanced plant growth. Positive relationship between microbial activity, soil nutrient cycling, and plant growth was demonstrated.